How Ramadan and Global Pandemic Affect Religiosity and Donating Behaviors - Moch. Khoirul Anwar; Ahmad Ajib Ridlwan; Prayudi Setiawan Prabowo; Ach. Yasin; A'rasy Fahrullah (Shirkah: Journal of Economics and Business, 2020)
Ramadan in the year of 2020 is the witness of global pandemic caused by the spread of Covid-19 that significantly alters human behaviors. In response to the current phenomenon, the present study is conducted to scrutinize how the holy month of Ramadan and global pandemic affect human religiosity and donating behaviors. To this end, this study employed a web-based questionnaire to gather the required data from 128 Indonesians who were voluntarily participated upon invitation. Using WarpPLS to analyze the data, the results showed that there was a significant influence of global pandemic situation and Ramadan on the level of religiosity. Moreover, the pandemic situation also encouraged the exist growth of donation institutions. This study further revealed the positive impact of the holy month of Ramadan and religiosity on human donating behaviors. In other words, Ramadan and global pandemic increased the level of human religiosity and the existence of donation institutions, as a results, their donating behaviors were also improved. However, this study found that the existence of donation institutions did not have any influence on human donating behaviors. These results offer an implication that Ramadan and global pandemic obviously provide a direct impact on religiosity and human donating behaviors.